Study of Ultrasound-assisted Acid Hydrolysis to Obtain Quercetin and their Antioxidant Activities from some Plants - Hoang, Le Huy; Phuong, Pham Thi; Hanh, Nguyen Thi; Do, Ho Ba; Huy, Nguyen Quang (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 4, 2019)
In this study, acidic hydrolysis to release the aglycone quercetin from plant extracts under ultrasound-assisted conditions was investigated. Based on the stability of quercetin, the suitable conditions were as follows: methanol/H 2 O (50:20, v/v) was added to the powder plants (ratio 50:1, ml/g), these mixtures were placed in ultrasonic bath of 37 kHz/550W; kept at 70°C within 30 min and then filtered. The filtrate was acidified with HCl (70:8, ml/ml). Lastly, the ultrasonication was carried out for hydrolysis for 1 hour (the second ultrasound) to obtain quercetin. We have obtained quercetin containing hydrolyzed extract from 10 plants to determine quercetin concentrations (using the HPLC optimized conditions) and evaluate the antioxidant activity (the capability to scavenge the DPPH radical). In 10 samples of plants that were obtained, both quercetin concentrations and antioxidant activity in the plant extract of the flower buds of Sophora japonica L have the highest value, then to the plant extract of Nelumbo nucifera Gaertn. In the Sophora flower-bud and the lotus leaf, quercetin content is calculated on dry material (mg/100g), 15423.04 and 5190.82  respectively; the average percentage inhibition of DPPH 100 µM (%) 55.26% and 32.23%., respectively. Keywords : Quercetin, HPLC, acid hydrolysis, ultrasound-assisted, antioxidant activity. References [1] S.G. Dmitrienko, V.A. Kudrinskaya, V.V. Apyari, Methods of extraction, preconcentration, and determination of quercetin, Journal of Analytical Chemistry 67 (4) (2012) 299-311. https://doi.org/ 101134/S106193481204003X. [2] H. Nishimuro, H. Ohnishi, M. Sato, M. Ohnishi-Kameyama, I. Matsunaga, S. Naito, K. Ippoushi, H. Oike, T. Nagata, H. Akasaka, S. Saitoh, K. Shimamoto, M. Konori, Estimated daily intake and seasonal food sources of quercetin in Japan, Nutrients 7 (4) (2015) 2345-2355. https://doi.org/ 10.3390/nu7042345. [3] C. Zhao, X. Ren, C. Li, H. Jiang, J. Guan, W. Su, Y. Li, Y. Tian, T. Wang, S. Li, Coupling ultrasound with heat-reflux to improve the extraction of quercetin, kaempferol, ginkgetin and sciadopitysin from Mairei Yew leaves, Applied Sciences 9 (4) (2019) 795-810. https://doi.org/10.3390/app9040795. [4] J. Azmir, M.S.I. Zaidul, M.M. Rahman, K.M. Sharif, A. Mohamed., F. Sahena, A.H.M. Jahurul, K. Ghafoor, N.A.N. Norulain, K.A.M. Omar, Techniques for extraction of bioactive compounds from plant materials : A review, Journal of Food Engineering 117 (4) (2013) 426-434. https://doi. org/10.1016/j.jfoodeng.2013.01.014. [5] L.H. Hoang, D.T.H. Anh, D.T. Hue, T.T.K. Oanh, N.Q. Huy, Determination of Quercetin Aglycone in Flos Sophorae japonicae Extract by High Performance Liquid Chromatography, VNU Journal of Science: Natural Sciences and Technology 33 (1S) (2017) 214-223 (in Vietnamese). https://doi.org/10.25073/2588-1140/ vnunst.4534. [6] A.M. Nuutila, K. Kammiovirta, M. Oksman-Caldentay, Comparison of methods for the hydrolysis of flavonoids and phenolic acids from onion and spinach for HPLC analysis, Food Chemistry 76 (4) (2002) 519-525. https://doi.org/ 10.1016/S0308-8146(01)00305-3. [7] L. Qiao, Y. Sun, R. Chen, Y. Fu, W. Zhang, X. Li, J. Chen, Y. Shen, X. Ye, Sonochemical effects on 14 flavonoids common in citrus : Relation to stability, Plos One 9 (2) (2014) e87766. https://doi. org/10.1371/journal.pone.0087766. [8] W. Brand-Williams, M.E. Cuvelier, C. Berset, Use of a free radical method to evaluate antioxidant activity, LWT - Food Science and Technology 28 (1995) 25-30. https://doi.org/10.1016/S0023-6438 (95)80008-5. [9] M. Biesaga, Influence of extraction methods on stability of flavonoids, Journal of Chromatography A 1218 (2011) 2505-2512. https://doi.org/10.1016/ j.chroma.2011.02.059. [10] L. Paniwnyk, E. Beaufoy, J.P. Lorimer, T.J. Manson, The extraction of rutin from flower buds of Sophora japonica, Ultrasonics Sonochemistry 8 (3) (2001) 299-301. https://doi.org/10.1016/S1350 -4177(00)00075-4. [11] X. He, Y. Bai, Z. Zhao, X. Wang, J. Fang, L. Huang, M. Zeng, Q. Zhang, Y. Zhang, Z. Zheng, Local and traditional uses, phytochemistry, and pharmacology of Sophora japonica L.: A review, Journal of Ethnopharmacology 187 (2016) 160-182. https://doi.org/10.1016/j.jep.2016.04.014. [12] I.Y. Bae, B.Y. Kwak, H.G. Lee, Synergistic antiradical action of natural antioxidants and herbal mixture for preventing dioxin toxicity, Food Science and Biotechnology 21 (2) (2012) 491-496. https://doi.org/10.1007/s10068-012-0062-9.